Evaluation of the Rain Effects on Gap Acceptance Behavior at Roundabouts by a Logit Model. (11th July 2018) - Lee, Dongmin; Hwang, Sooncheon; Ka, Eunhan; Lee, Chungwon
Abstract : A roundabout is generally known as an efficient, safe, and environmentally friendly intersection. Since 2010, the Korea government has taken the lead in constructing roundabouts as part of a special project. During that time, many ideas have been put forward to improve the safety, operation, and design of such roundabouts. In terms of improvements, it is particularly important to understand roundabout gap acceptance behavior. As such, we investigated gap acceptance behaviors at four roundabouts based on field observation during both good weather and rainy conditions. Based on the observed data, roundabout critical gaps were estimated, and a logit model for gap acceptance using various roundabout variables was developed to investigate gap acceptance maneuvering at roundabouts. A total of 2, 421 data events for gap acceptance were collected from the field observation. Out of these events, 64.6% of drivers (1, 564 drivers) accepted the given gaps and 35.4% of drivers (857 drivers) rejected them. The values for critical gaps were estimated using several different estimation methods and ranged from 3.3 to 4.7 seconds. The model was developed using four variables including gap size, type of circulating vehicle, traffic volume at the circulating lane, and weather conditions. The developed model shows that a longer gap results in a 3.669 times higher probability of entering roundabouts when the gap is sufficiently great for acceptance than when the gap is smaller. The effects of other variables, such as circulating vehicle types, circulating traffic volume, and weather conditions, are relatively lower than that of a gap size. Rain conditions influenced gap acceptance maneuvering around a roundabout. Drivers need about a 10 percent longer gap to accept entry into roundabouts during rainy conditions, and gap acceptance probabilities are 10 to 20 percent lower for the same given gap time during rainy conditions compared to good weather conditions.